Penerapan Perpustakaan Digital Dan Pelatihan Motivasi Diri Sebagai Adaptasi Pola Belajar Siswa Di Masa Pandemi Covid-19 - Ulfah Khaidarni; Lista Fauziah; Yayan Saryani; Hairun Nisa; Ail Muldi; Mulyani Pratiwi SW; Neka Fitriyah (Peneliti.net, 2022)
During the Covid-19 pandemic, State Junior Highs School 1 Menes implemented a distance learning system or use internet network. The obstacles that occur cause unfavorable behavior for students, such as decreased student motivation, poor relationships between parent and students and decreased student achievement. The purpose of this service activity is to change student behavior for the better by conducting good communication training to parents, providing motivation to learn through games and introducing digital library applications to increase reading interest and as a reference for students learning at home that researchers do face to face. The method used in this study is a mix method, which combines quantitative and qualitative research methods simultaneously. Based on the results of empowerment activities that have been carried out on students in order to help improve the quality of learning and student achievement, we carried out measurement of change through pre-test and post-test where the comparison value between pre-test and post-test was considered to indicate a change in thinking patterns. Students who are expected to change the pattern of student behavior for the better in motivating themselves to students in order to increase their interest in learning and be able to communicate well with their parents in order to meet their needs in online learning.